1980
DOI: 10.1093/nar/8.20.4709
|View full text |Cite
|
Sign up to set email alerts
|

Ordered distribution of modified bases in the DNA of a dinoflagellate

Abstract: In DNA of the dinoflagellate Crypthecodinium cohnii, 38% of the thymine is replaced by the modified base 5-hydroxymethyluracil, and approximately 3% of the cytosine is replaced by 5-methylcytosine. Both of the modified bases are non-randomly distributed in the DNA. Determinations of 3' nearest neighbors show that HOMeU is preferentially located in the dinucleotides HOMeUpA and HOMeUpC. Pyrimidine tract analysis shows that HOMeU is also greatly enriched in the trinucleotide purine-HOMeU-purine. As in other euka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
2

Year Published

1980
1980
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 34 publications
1
19
2
Order By: Relevance
“…4). In agreement with previous studies, we found that these dinoflagellates contain 5-MeCyt and have replaced a substantial fraction of Thy with HOMeUra (10,11,19). Diplonema DNA also contained a spot that migrates at the position of 5-Me-dCMP (see below) whereas no DNA methylation was FIG.…”
Section: Resultssupporting
confidence: 92%
“…4). In agreement with previous studies, we found that these dinoflagellates contain 5-MeCyt and have replaced a substantial fraction of Thy with HOMeUra (10,11,19). Diplonema DNA also contained a spot that migrates at the position of 5-Me-dCMP (see below) whereas no DNA methylation was FIG.…”
Section: Resultssupporting
confidence: 92%
“…A fragment -2 kb in length is also found in the hybridization patterns of all of the DNAs (Fig. IB), and has also been shown to hybridize only with 17s rRNA in WHd (24). It is slightly smaller in WHd/PS rDNA than in the rDNA of the other isolates.…”
Section: Resultsmentioning
confidence: 78%
“…The 1.35 kb fragment present in the WHd strain and the Puget Sound isolate (Fig. IB) has been shown to contain only 24s RNA coding sequences (24). A fragment of this size is absent from the DNAs of the other isolates, but they have hybridizing Hind 111 fragments of sizes not found in WHdlPS rDNA.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations